Fiber Supercontinuum Source for Broadband-CARS Microspectroscopy Based on a Dissipative Soliton Laser - Yan Li; Xiaosheng Xiao; Lingjie Kong; Changxi Yang (IEEE Photonics Journal)
We propose and demonstrate a supercontinuum fiber laser source for broadband coherent anti-Stokes Raman scattering (BCARS) microspectroscopy, seeded by a Yb-doped dissipative soliton fiber laser. Smooth continuum Stokes pulses ranging from 1050 to 1312 nm at –20 dB bandwidth are generated in a highly nonlinear fiber from the compact fiber seed, and the corresponding pump pulses are obtained after a narrowband filter centered at 1036 nm. With this fiber laser source, we are able to obtain BCARS spectra in 700–1900 cm–1 spectral range simultaneously with resolution less than 10 cm–1, and show its application in analyzing complex mixture. We also demonstrate the capability of our system in chemical imaging by simultaneously obtaining two two-dimensional CARS images of retinoic acid crystal at Raman shifts of ∼1574 and ∼1162 cm–1, respectively.